Does Competition Cause Stability in Banks? SFA and GMM Application to Sub-Saharan Africa Commercial Banks - Akande, Joseph Olorunfemi; Kwenda, Farai (Journal of Economics and Behavioral Studies, 2017)
Investigating the competition-stability view in relation to the banking sector, the intention behind this study was to find out how far efficiency is associated with a competitive banking environment and if it warrants the continued agitation towards fostering increased competition in banking markets around the world. This view has significant support in spite of the potential instability that could possibly result from risk appetite, which the competition-fragility view holds to be associated with competition. We employed a stochastic frontier analysis (SFA) to model an instrumental variable of competition resulting from increased efficiency or inefficiency due to bank-level competition, which we used in the regression of competition against stability using the generalized method of moments (GMM). We found that competition increased the efficiency of the banking sector over the study period. The regression results of our instrument against stability in the Sub-Saharan Africa region was found to be positive and strongly significant with stability providing evidence of transmission from competition to efficiency to stability, and, hence consistent with competition-stability views. Our conclusion is that while competition is desirable, it must be optimized to enhance efficiency without which the effects become detrimental. Therefore, there must be ongoing regulation to check excessive competition.